ICT BARRIERS IN EFL REMOTE EDUCATION: COMPARATIVE EXPERIENCES OF SENIOR HIGH SCHOOL TEACHERS ACROSS SCHOOL TYPES IN WEST JAVA, INDONESIA - Eddraoui, Bouchra; Sukyadi, Didi; Bukhori Muslim, Ahmad; Musthafa, Bachrudin (English Review: Journal of English Education, 2025)
The COVID-19 pandemic has disrupted education globally. In response, the Indonesian government mandated an immediate transition to virtual teaching. However, the rapid transformation was associated with unprecedented challenges and complications. This qualitative study investigates the experiences of 24 EFL senior high school teachers in West Java, Indonesia, representing diverse school backgrounds. The study illustrated that the teachers faced various challenges categorised into three significant aspects: 1-Technological/Technical (equity and accessibility, bandwidth, technological support), 2- Students (lack of motivation, time management, changed behaviour), and 3-Facilitator's abilities (limited ICT abilities, burnout, workload). Specifically, urban public high school teachers failed to keep students engaged and motivated in online classrooms. In contrast, rural public senior high school instructors encountered severe technical hurdles, such as inadequate internet access and limited digital equipment, making it challenging to prepare interactive classes. Furthermore, private senior high school instructors were unprepared for online education and battled to keep their pupils engaged and motivated. Furthermore, private Islamic school teachers had a particular issue connecting their teaching techniques with Islamic beliefs, which complicated digital tools and platforms. The study suggests that EFL teachers require extensive support networks, focused interventions, and specialised training to address these issues.